Community Rehabilitation and Hospitalizations Among People With Chronic Psychotic Disorder: Is There a Differential Association by Co-occurring Substance Use Disorder? - Florentin, Sharon; Rosca, Paola; Bdolah-Abram, Tali; Neumark, Yehuda (Frontiers in Psychiatry, 2021)
Objective – Co-occurrence of chronic psychotic disorders and substance use disorder (SUD) is clinically challenging and increasingly prevalent. In 2000, Israel passed legislation Israel to foster rehabilitation and integration in the community of persons with mental health disorders. In 2010, the need to allocate resources for patients with these co-occurring disorders (COD) was officially recognized. Yet, most community-based rehabilitation services were not specifically designed for COD. This study examines the relationship between duration of community rehabilitation and patterns of psychiatric hospitalizations among persons with and without COD. Methods – Data from the National Psychiatric Case Register (NPCR) on 18,684 adults with schizophrenia/schizoaffective disorders hospitalized in 1963-2016 (at least once in 2010-2015), was merged with data from the Israel Mental Rehabilitation Register (IMRR). Associations and interactions between COD-status (COD/non-COD), time-period (Period1: 2001-2009, Period2: 2010-2016), duration of housing or vocational rehabilitation and on hospitalization measures were analyzed using repeated-measures ANOVA. Results – The proportion of non-COD chronic psychotic patients who received rehabilitation services increased from 56% in Period1 to 63% in Period2, as it did among COD patients - 30% and 35%, respectively. The proportion of non-COD patients who received longer-duration vocational rehabilitation (≥ one year) was significantly higher (43%) than among COD patients (28%) in both time periods. For housing rehabilitation, these rates were 79% and 68%, respectively. Persons with COD experienced more hospitalization days annually than non-COD patients. Duration of rehabilitation (less/more than a year) was inversely associated with the annual number of hospitalization days (p<0.0001). This pattern was noted in both COD and non-COD groups. Conclusions – COD patients with prolonged rehabilitation seemingly achieve long-term clinical improvement similar to non-COD patients, despite most rehabilitation settings in Israel not being specifically designed for COD patients. Yet, COD patients receive overall less rehabilitation services and for shorter periods than non-COD patients. It is thus advisable to provide long-term rehabilitation services to patients with COD, who may need more time to commit to treatment. To achieve better long-term mental health improvements – individually and nationally, a continued expansion of community-based integrative treatment and rehabilitation services for COD patients is needed in Israel.